A laboratory experimental technique for simulating combined blast and impact loading. (December 2019) - Li, Lang; Zhang, Qian-Cheng; Zhang, Rui; Wang, Xin; Zhao, Zhen-Yu; He, Si-Yuan; Han, Bin; Lu, Tian Jian
Highlights: A novel composite projectile for simulating combined blast and impact loading has been proposed. The composite-projectile-based approach is proved to be valid in simulating combined loadings from cased explosives under certain conditions. Based on the experimental approach, a new synergetic effect of combined blast and single fragment impact loading is found. The proposed approach provides a chance to investigate ballistic impact of deforming target experimentally. Abstract: A novel composite projectile is put forward to simulate combined blast and single fragment impact loading, which is comprised of a cylindrical aluminum foam projectile embedded with a fragment simulation projectile (FSP). Comparison between cased explosive and composite projectile in terms of the generated combined loading shows that the composite projectile technique is theoretical feasible. Experimental tests for normal impact of the composite projectile on clamped plates are carried out. Results show that the proposed composite projectile can induce both blast-induced deflection and fragment-induced perforation on the clamped plate. The arrival time interval between blast and fragment has significant influence on the extent of induced damage on the plate and the residual FSP velocity. Numerical simulations with the method of finite elements are carried out to provide further insight into the interaction between the composite projectile and clamped plate, and to explain observations and measurements in experiments. The present study reveals a new synergetic effect of combined blast and single fragment impact loading on clamped plate: arrival time interval between blast and impact loading affects significantly the residual velocity of the FSP.